How do perceived and objective measures of neighbourhood disadvantage vary over time? Results from a prospective-longitudinal study in the UK with implications for longitudinal research on neighbourhood effects on health - Yakubovich, A; Heron, J; Humphreys, D (Public Library of Science, 2020)
Background Theories of health outcomes often hypothesize that living in more socially and economically disadvantaged neighbourhoods will lead to worse health. Multiple measures of neighbourhood disadvantage are available to researchers, which may serve as better or worse proxies for each other across time. To inform longitudinal study design and interpretation we investigated how perceived and objective measures of neighbourhood disadvantage vary over time and the factors underlying this variation.